Helicobacter pylori SlyD stabilizes TPT1 via hnRNPK and enhances OCT1-mediated CDX2 transcriptional activation to drive gastric intestinal metaplasia - Shuwen Zheng; Yingying Wang; Chuxuan Ni; Rui Guo; Xunan Qiu; Jijun Chen; Lu Wang; Xiaohu Sun; Moye Chen; Yunen Liu; Yuan Yuan; Yuehua Gong (BMC Medicine, 2025)
Abstract Background Gastric intestinal metaplasia (GIM) represents an important precancerous lesion in intestinal-type gastric cancer, triggered by persistent Helicobacter pylori (H. pylori) infection. In a previous study, we unveiled SlyD as a novel virulence factor of H. pylori, establishing its role in GIM induction through TPT1. However, the underlying mechanism remains undetermined. Methods Gastric epithelial cells were stimulated with H. pylori 26695, a SlyD inactivated mutant (ΔSlyD), and purified HpSlyD protein, respectively. Real-time qPCR and western blot were subsequently used to assess the expression levels of hnRNPK, TPT1, OCT1, and GIM markers. RNA sequencing was employed to identify differentially expressed genes associated with H. pylori SlyD infection. Protein stability was evaluated using cycloheximide. Molecular interactions were investigated through co-immunoprecipitation, chromatin immunoprecipitation, and dual-luciferase reporter assays. Additionally, molecular docking was utilized to predict TPT1 inhibitors. Immunohistochemistry staining was conducted to validate hnRNPK, TPT1, OCT1, and CDX2 expression in gastric tissue samples from both human and Mongolian gerbils. Results H. pylori SlyD upregulates TPT1 and induces the expression of GIM markers through hnRNPK. The interaction between hnRNPK and TPT1 enhances TPT1 protein stability, with H. pylori SlyD intensifying this association. TPT1 promotes the expression of GIM markers mediated via OCT1, which binds to CDX2 promoter region, thereby modulating its transcriptional activity. Dihydroartemisinin has the potential to target TPT1, inhibiting the H. pylori SlyD-induced expression of GIM markers. Conclusions In vitro and in vivo experiments verified that H. pylori SlyD enhances TPT1 stability through hnRNPK, leading to OCT1-mediated transcriptional activation of CDX2 and the initiation of the GIM process. Our study offers novel perspectives on the pathogenesis of H. pylori-related gastric precancerous conditions.